Cardiac catheterization activity in pediatric cardiac transplantation. Can catheterization needs be predicted? - Freixa-Benavente, Andrea; Dolader, Paola; Gran, and, Ferran; Betrián-Blasc, Pedro (REC, Interventional cardiology (Internet. English ed.), 2024)
ABSTRACT Introduction and objectives: Although cardiac catheterization (CC) has become a routine practice in pediatric heart transplantation (HT), there is still a shortage of widely used protocols and strong evidence on the number of procedures required and their impact on HT outcomes, as well as the need for further CC. This study aimed to analyze CC activity in pediatric HT recipients in a tertiary center and describe risk factors for a higher number of post-HT procedures. Methods: This retrospective study obtained data from medical reports and image files. The sample was composed of patients with cardiomyopathies and congenital heart diseases (CHD). Risk factor analysis for CCs was conducted with linear regression and the ANOVA test. Results: The sample included 61 children (36.07% with CHD). The CHD group had a higher mean number of CCs prior to HT. The most frequent activities prior to HT were diagnostic catheterizations, followed by endomyocardial biopsies for cardiomyopathies and aortopulmonary collaterals in CHD patients. There were 389 post-HT CCs (608 procedures). Most CCs were performed for rejection surveillance, accounting for 92.75% of procedures. The univentricular CHD subgroup was associated with a higher number of CC after HT (P = .03). Conclusions: Despite long life expectancy, pediatric HT recipients have...